INSIDER OWNERSHIP, FREE CASH FLOW, DAN PERTUMBUHAN TERHADAP DIVIDEND PAYOUT RATIO - Yessri Meiliyawati; Ellen Rusliati (JRAK, 2020)
Dividend alongside capital gain is a return for stock holder. The aim of this study is to determine the condition of insider ownership, free cash flow, growth and dividend payout ratio, and to determine their effect of insider ownership, free cash flow and growth simultaneously and partially on dividend payout ratio. The population were mining companies sector listed in Indonesia Stock Exchange in the period of 2010-2017. The sample of this study is amounted to 4 companies with the amount of observations were 32. The method used were descriptive and verificative using panel data regression. The results showed that simultaneously insider ownership, free cash flow and growth has significant effect on dividend payout ratio with contribution of effect 68.19%. Partially, insider ownership has a significant positive effect, free cash flow and growth have significant negative effect on dividend payout ratio.